Synthesis of new sulfonylamide derivatives of isoxazole via ring-closing metathesis - Pavliuk, O.V.; Holovatiuk, V.M.; Bezugly, Yu.V.; Kashkovsky, V. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
The new series of diallyl sulfonylamides were synthesized. The ring-closing metathesis reactions of isoxazole diallylamidosulfonyl derivatives are carried out, by using a ruthenium carbene catalyst for the first time. The perspective of the synthesis of new pyrroline-containing sulfonylamide isoxazole derivatives by this reaction has been shown.